2021
DOI: 10.3390/app11198887
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Release from Biomass Particles during Combustion—Real-Time In Situ TDLAS Detection and Numerical Simulation

Abstract: Potassium (K) is one of the main and most hazardous trace species released to the gas-phase during thermochemical conversion of biomass. Accurate experimental data and models of K release are needed to better understand the chemistry involved. Tunable diode laser absorption spectroscopy (TDLAS) is used for simultaneous real-time in situ measurements of gas-phase atomic K, water (H2O) and gas temperature in the vicinity (boundary layer) of biomass particles during combustion in a laboratory single-particle reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…This is in agreement with other experiments on a small batch of biomass particles where the maximum K-release was observed during the combustion stage. 21 , 32 The evaporation and dissociation of K 2 CO 3 and K 2 SO 4 continue during the gasification stage, but the release of K from K 2 CO 3 has a higher rate. The gasifier has a high water vapor concentration, so the dissociation rate of the salts will be orders of magnitude higher than their evaporation rate, 19 which leads to a high amount of KOH formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with other experiments on a small batch of biomass particles where the maximum K-release was observed during the combustion stage. 21 , 32 The evaporation and dissociation of K 2 CO 3 and K 2 SO 4 continue during the gasification stage, but the release of K from K 2 CO 3 has a higher rate. The gasifier has a high water vapor concentration, so the dissociation rate of the salts will be orders of magnitude higher than their evaporation rate, 19 which leads to a high amount of KOH formation.…”
Section: Resultsmentioning
confidence: 99%
“…The release of alkali metals and inorganic elements from biomass is commonly studied in lab-scale apparatus on a small batch of biomass particles under pyrolysis, combustion, or gasification conditions. , In most experiments, the K content in the solid, as the most abundant alkali metal in biomass, was measured before and after the experiments to calculate the K-release at different operating conditions. , It was found that, other than temperature and water vapor concentration, CO 2 concentration surrounding the particle is important as it prohibits the K-release . On the other hand, the type of biomass and the composition of the ash-forming elements are also important, since, for instance, Cl and S facilitate while silicon (Si) and aluminum (Al) hinder the K-release .…”
Section: Introductionmentioning
confidence: 99%
“…Zhechao Qu et al used TDLAS for simultaneous in-suit detection of K atoms, water in gas phase and temperature near bio-particles in the process of burning of the laboratorial single-particle reactor. For the first time, the K release behavior of willow and wheat straw was compared with the numerical model considering K/S/Cl interaction in ash, proving fine linearity between the simulated and measured K concentration in the devolatilization stage [30]. Yong Bao et al developed a relative entropy tomographic reconstruction (RETRO) algorithm to solve errors of TDLAS in in-situ combustion, retrieved the reconstructed double-line absorbance distribution, and verify feasibility of this algorithm through performing numerical simulations and proof-of-concept tests [31].…”
Section: Gas Detectionmentioning
confidence: 88%
“…Atomic K imaging has previously been performed using spontaneous emission and laser-induced fluorescence. , Imaging of KOH/KCl and K 2 SO 4 aerosols has been achieved by photofragmentation fluorescence spectroscopy and Mie scattering, respectively. One drawback of the techniques mentioned above is the need for calibration procedures to obtain species concentrations, which is important for, e.g., the validation of numerical particle models …”
mentioning
confidence: 99%
“…One drawback of the techniques mentioned above is the need for calibration procedures to obtain species concentrations, which is important for, e.g., the validation of numerical particle models. 21 …”
mentioning
confidence: 99%